ICELAND AS AN IMAGINARY PLACE IN A EUROPEAN CONTEXT - SOME LITERARY REPRESENTATIONS. - Egilsson, Sveinn Yngvi (Tijdschrift voor Skandinavistiek, 2018)
The article focuses on the image of Iceland and Iceland as an imaginary place in literature from the nineteenth century onwards. It is especially concerned with the aesthetics or discourse of the sublime, claiming that it is the common denominator in many literary images of Iceland. The main proponents of this aesthetics or discourse in nineteenth-century Icelandic literature are discussed before pointing to further developments in later times. Among those studied are the nineteenth-century poets Bjarni Thorarensen (1786-1841), Jonas Hallgrimsson (1807-1845), Grimur Thomsen (1820-1896) and Steingrimur Thorsteinsson (1831-1913), along with a number of contemporary Icelandic writers. Other literary discourses also come into play, such as representing Iceland as "the Hellas of the North", with the pastoral mode or discourse proving to have a lasting appeal to Icelandic writers and often featuring as the opposite of the sublime in literary descriptions of Iceland.